PENGARUH BUSYNESS, UKURAN DEWAN KOMISARIS, DAN KEAHLIAN KEUANGAN KOMITE AUDIT TERHADAP BIAYA AUDIT - Zaitul; Sari, Ayu Yulia; Puspa, Dwi Fitri; Rahmawati, Novia; ilona, Desi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
The audit fee is a measurement of audit quality, influencing the accounting quality. Previous research has been done largely using the Anglo-Saxon corporate governance system and fails to pay attention to the unique continental European corporate governance system, such as Indonesia. In addition, the busyness supervisory board has not yet been tested in this kind of economic environment.Â  This study investigates the relationship between supervisory board busyness and audit fee. In addition, this study also analyzed the effect of the supervisory board size and audit committee with financial Expertise on the audit fee. The agency and resource-dependent theory are applied to understand this relationship theoretically. Banks listed in Indonesia Stock Exchange are used in this study. Multivariate regression analysis is applied by considering the classical assumption first. The findings show no effect of the supervisory board's busyness on audit fees. However, the other two independent variables significantly affect audit fees. Supervisory board size has a positive impact on audit fees. Hence, the audit committee with financial Expertise is negatively related to the audit fee. This finding has theoretical implications for agency theory and resources-dependent theory. Practically, this result can be used by stakeholders to formulate the board composition in terms of busyness and size as well as the financial Expertise of the audit committee. Keywords: supervisory board busyness, supervisory board size, audit committee financial expertise, audit fee Â